Exploring and Harnessing Haplotype Diversity to Improve Yield Stability in Crops - Qian, Lunwen; Hickey, Lee T.; Stahl, Andreas; Werner, Christian R.; Hayes, Ben; Snowdon, Rod J.; Voss-Fels, Kai P. (Frontiers in Plant Science, 2017)
Abstract In order to meet future food, feed, fibre and bioenergy demands, global yields of all major crops need to be increased significantly. At the same time, the increasing frequency of extreme weather events such as heat and drought necessitate improvements in the environmental resilience of modern crop cultivars. Achieving sustainably increase yields implies rapid improvement of quantitative traits with a very complex genetic architecture and strong environmental interaction. Latest advances in genome analysis technologies today provide molecular information at an ultrahigh resolution, revolutionizing crop genomic research and paving the way for advanced quantitative genetic approaches. These include highly detailed assessment of population structure and genotypic diversity, facilitating the identification of selective sweeps and signatures of directional selection, dissection of genetic variants that underlie important agronomic traits, and genomic selection strategies that not only consider major-effect genes. Single-nucleotide-polymorphism (SNP) markers today represent the genotyping system of choice for crop genetic studies because they occur abundantly in plant genomes and are easy to detect. SNPs are typically biallelic, however, hence their information content compared to multiallelic markers is low, limiting the resolution at which SNP-trait relationships can be delineated. An efficient way to overcome this limitation is to construct haplotypes based on linkage disequilibrium (LD), one of the most important features influencing genetic analyses of crop genomes. Here, we give an overview of the latest advances in genomics-based haplotype analyses in crops, highlighting their importance in the context of polyploidy and genome evolution, linkage drag and, co-selection, We provide examples of how haplotype analyses can complement well-established quantitative genetics frameworks, such as quantitative trait analysis and genomic selection, ultimately providing an effective tool to equip modern crops with environment-tailored characteristics.